2008
DOI: 10.1002/dmrr.885
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glycooxidation protein products in type 2 diabetic patients with nephropathy

Abstract: The connection between plasma levels of both glycooxidation protein products-AGE and AOPP with nephropathy severity, measured by the degree of albuminuria, in T2DM patients was observed. We can suggest that the AOPP better reflect the progression of kidney damage than AGE in examined diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Plasma was initially analysed using a previously published AOPP method [8–10, 12, 17]. Of the 77 plasma samples assessed from both diabetic patients and nondiabetic control subjects, only 27 produced an interreplicate CV of less than 20%, and only six of these were under 10% (see Supplementary Material 1 available online at http://dx.doi.org/10.1155/2015/496271).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma was initially analysed using a previously published AOPP method [8–10, 12, 17]. Of the 77 plasma samples assessed from both diabetic patients and nondiabetic control subjects, only 27 produced an interreplicate CV of less than 20%, and only six of these were under 10% (see Supplementary Material 1 available online at http://dx.doi.org/10.1155/2015/496271).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have found that AOPP are moderately elevated in adult patients with Type 1 diabetes and more markedly elevated in those with Type 2 diabetes [8, 9], although others have suggested that AOPP are only significantly increased in Type 2 diabetes [10]. They have been reported to be elevated in Type 2 diabetes [11], and the concentration correlated with insulin resistance [12] or the presence and/or severity of diabetic complications [13, 14], such as retinopathy [15, 16] or nephropathy [17]. In juveniles and adolescents with Type 1 diabetes, AOPP were found to accumulate over time and were significantly associated with disease duration [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it has been reported that MDA levels have increased in type 2 DM. 9 However, there are many hypotheses about the possible mechanisms involved in lipid peroxidation increase such as hypercholesterolemia, 34 hypertriglyceridaemia, 22 and the formation of AGEs. 35 Similar to the study of Komosinska et al, 36 we also found a significantly positive correlation between MDA levels and HbA 1c concentration, which suggests that hyperglycemia could also be a probable mechanism involved in the increased MDA levels, in type 2 DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…9,16 AOPP levels was related with poor glycaemic control, obesity, lipid disorders, duration of disease (longer than 10 years), and diabetic complications including nephropathy. 4,16,17 IMA levels were also higher in diabetic patients, especially those with complications, and was related to the levels of HbA1c. 9 In diabetes, the most frequent complication is diabetic nephropathy (DN), which is the most common cause of end-stage renal disease, requiring dialysis, and it shortens human life.…”
mentioning
confidence: 90%